Morfologi dan Morfometri Nematoda Sista Kentang (Globodera spp.) Asal Dataran Tinggi Dieng, Jawa Tengah - Auliya Selamet; Supramana Supramana; Meity Suradji Sinaga; Ali Nurmansyah; Kikin Hamzah Mutaqin (Jurnal Fitopatologi Indonesia, 2019)
The Morphology and Morphometry of Potato Cyst Nematodes (Globodera spp.) from Dataran Tinggi Dieng, Central JavaIn Indonesia, the potato cyst nematode (PCN) was first reported in 2003, at potato plantation in Batu, East Java. Golden cyst (Globodera rostochiensis) was detected in Bandung, West Java; Banjarnegara, Central Java; Batu, East Java; and Gowa, South Sulawesi, whereas the pale cyst (G. pallida) has been reported at limited distribution in Dataran Tinggi Dieng (Central Java). The aim of this research was to identify the Globodera species of Dataran Tinggi Dieng based on morphological and morphometrical methods. Soil samples were collected from Dieng plateau at 30 selected potato plantations ranging from 1 100 – 2 100 m above sea level. The identification of PCN was done by observing the morphological and morphometrical key characters of cysts and second juveniles (J2). Two species of Globodera, that are G. rostochiensis and G. pallida, were identified from soil samples. The key characters of G. pallida including distinct forward projection of J2 stylet knob, granek’s ratio value less than 3, and number of cuticular ridges between vulval basin and anus are less than 12 were identified. There were 25 specimens that having granek’s ratio less than 3, and 10 specimens having cuticular ridges number less than 12. G. rostochiensis which has the shape of a stylet knob protrudes posteriorly and the value of the granek’s ratio greater than 3.5 was identified in 30 specimens.